Hölderlin’s Theory of Tragedy (Revista Eletrônica Estudos Hegelianos, 2021)
This article examines some theoretical texts of Hölderlin on the function and historical task of tragedies, esp. the Grund zum Empedokles and the annotations to Sophocles. The tragedy is for Hölderlin a form of transition from antiquity to modernity. Through the individual tragical the historical occurs.